A cross sectional study of renal involvement in tuberous sclerosis. Issue 6 (June 1996) - Cook, J A; Oliver, K; Mueller, R F; Sampson, J
Abstract : Renal disease is a frequent manifestation of tuberous sclerosis (TSC) and yet little is known about its true prevalence or natural history. We reviewed the notes of 139 people with TSC, who had presented without renal symptoms, but who had been investigated by renal ultrasound. Information on the frequency, type, and symptomatology of renal involvement was retrieved. The prevalence of renal involvement was 61%. Angiomyolipomas were detected in 49%, renal cysts in 32%, and renal carcinoma in 2.2%. The prevalence of angiomyolipoma was positively correlated with age, compatible with a two hit aetiology. Renal cysts were the commoner lesion in young children, and their prevalence did not appear to be age related. Renal investigation in people with TSC had been inconsistent and limited. We suggest guidelines for renal investigation in those with TSC.